Echoes of Rituals of Initiation and Blood Sacrifice in Heart of Darkness by Joseph Conrad - Wicher, Andrzej (Text Matters: A Journal of Literature, Theory and Culture, 2022)
In Heart of Darkness, the protagonist Kurtz, of whom we do not, in fact, see much, is shown as connected with a native “sorcerer,” a “witch-man,” who had “antelope horns” on his head. Antelopes, or goats, are typical sacrificial animals, and the protagonist of this novella is a European who perishes in the midst of tropical forests, in spite of the high hopes that accompany his decision to try his luck in an exotic environment. Kurtz has promising beginnings, but later he gradually degenerates, carrying out what may be called a reversal of the ritual of initiation, comparable to the inverted ritual, to use V. Propp’s term, in folklore. In this sense, he may be regarded as a counterpoint to Conrad himself whose life can easily be described as a modern and uncommonly successful enactment of the same ritual. Meanwhile, Kurtz’s, and to a lesser extent also Marlow’s, failure as initiates is inscribed in the failure of the European civilization to construct a European empire in Africa.